Comparative Study of the Wind Codes: An Application to Forty-Six Storied Wall-Frame Structure - Kiriparan, B.; Jayasinghe, J.A.S.C.; Dissanayake, U.I. (The Institution of Engineers, Sri Lanka, 2022)
Wind is a random movement of air particles in both time and space, which produces very complicated dynamic loading scenario on flexible structures like tall buildings. Modern tall buildings are becoming more slender, flexible, lightweight and irregular in shape due to revolution of associated technologies. Consequently, analysis of tall buildings considering complicated nature of wind loading and dynamic response of the structural system is an important role in design of tall buildings. Wind tunnel test is the most reliable tool for the estimation of dynamic wind loading on tall buildings. However, due to the cost and time involved, wind design codes are generally used during the preliminary design stage. Thus, understanding the background of dynamic wind loading and procedures adopted in wind design standards to represent the dynamic effects is vital to arrive at an efficient, safe and economical structural system during the preliminary design stage. This paper presents an overview on background of dynamic wind loadings and provisions of four international wind codes frequently referred to in Sri Lanka, British Standard (BS), European Standard (BS EN), Australian Standard (AS/NZS) and Standard of Architectural Institute of Japan (AIJ). Further, the concept of equivalent static load derived based on the “gust-factor” method adopted in most of the international wind design codes is discussed. At the end, a forty-six storied wall-frame structure was used as the numerical example for the explanation of dynamic wind loading and its influence on the structural design.
Keywords: Tall building; Wind code; Along wind response; Across wind response; Torsional wind responses